JOLOTUNDO LESTARI: HARMONY OF NATURE CONSERVATION AND LOCAL WISDOM OF MAJAPAHIT HERITAGE - Rahmawati, Mei Indah (PT Altin Riset Publishing, 2025)
Jolotundo is one of the heritage sites of the Majapahit Kingdom, which has high cultural and ecological value. This study aims to examine the role of local wisdom in environmental conservation in the Jolotundo area through literature study methods and questionnaires. The research was carried out in Lebak Hamlet, Lebaksono Village, Pugging District, Mojokerto Regency, involving 165 respondents. The results of the analysis show that the community has a high awareness of the importance of maintaining spring water, cultural traditions, and environmental cleanliness. This study found that local traditions such as Ruwat Petirtaan rituals and gotong royong activities make a great contribution to sustainable preservation. These findings confirm the importance of collaboration between the government and the community in maintaining ecological and cultural values. This research highlights the relevance of integrating local wisdom in conservation strategies as a sustainable approach to heritage areas.